Idiopathic pulmonary fibrosis: Physician and patient perspectives on the pathway to care from symptom recognition to diagnosis and disease burden. Issue 1 (5th October 2021) - Lancaster, Lisa; Bonella, Francesco; Inoue, Yoshikazu; Cottin, Vincent; Siddall, James; Small, Mark; Langley, Jonathan
Abstract: Background and objective: Idiopathic pulmonary fibrosis (IPF) is a chronic progressive disease that requires ongoing care and is associated with considerable socioeconomic burden. We evaluated the IPF care pathway from symptom recognition to treatment. We describe the impact of IPF on healthcare resource use (HCRU), quality of life (QoL) and work impairment, and report differences in patient and physician perspectives using real‐world data from France, Germany, Japan and the United States. Methods: Quantitative, point‐in‐time data were collected as part of the Adelphi IPF II Disease Specific Programme™. Physician‐reported data (patient demographics, medical history, diagnoses, treatment) were matched to patient‐reported data (HCRU, QoL, work impairment). HCRU was measured as physician visits and hospitalizations. QoL and work impairment were measured using the EuroQol‐5 Dimensions (EQ‐5D) and Work Productivity and Activity Impairment questionnaires. Results: Overall, 244 physicians reported data on 1249 patients, 739 of whom self‐reported data. Diagnostic delays of 0.8 (Germany) to 2.0 (Japan) years after symptom onset were reported; treatment initiation was further delayed. In all countries, patients more often reported symptoms in the survey than did their physicians. On average, patients underwent 7–10 clinical tests before diagnosis. Antifibrotic use increased from 57% (2016) to 69% (2019); only 50% of patients with moderate/severe IPF were satisfied with their treatment. The 12‐month hospitalization rates were 24% (Japan) to 64% (United States). Patients reported low QoL (mean EQ‐5D visual analogue scale: 61.7/100). Conclusion: Patients with IPF experience considerable diagnostic and treatment delays. More effective therapies and management are needed to reduce the disease burden. Abstract : Patients with idiopathic pulmonary fibrosis experience diagnostic delays that can negatively influence their prognoses. This study uses real‐world data from four countries to characterize the considerable diagnostic and treatment delays based on patients' experience. We describe the resultant socioeconomic burden, including effects on healthcare resource utilization, quality of life and work impairment. See related Editorial